Women’s Education and Family Self Reliance in Banten Province, Indonesia: An Analysis using the Geographically Weighted Regression (GWR) Method - Wiwik Puji Mulyani; Hannifa Irmajihan Nabilla; Irsyamaulina Hanif (Universitas Pendidikan Ganesha, 2026)
Family development initiatives in Indonesia have long emphasized family self-reliance as a core objective. However, limited empirical evidence explains how gender-oriented factors, particularly women’s education, shape family self-reliance across space. This study aims to assess the spatial distribution of women’s education and family self-reliance across sub-districts in Banten Province, and examine the extent to which women’s education influences family self-reliance while accounting for spatial heterogeneity. This research employs a quantitative cross-sectional design using secondary data at the sub-district level in Banten Province. The analysis consists of two stages. First, descriptive statistics are used to map and compare variations in women’s education and family self-reliance. Second, Geographically Weighted Regression (GWR) is applied to estimate local parameter coefficients and detect spatial non-stationarity in the relationship between women’s education and family self-reliance. The findings reveal a positive and statistically significant association between women’s education and family self-reliance. However, the magnitude of this effect varies considerably across sub-districts, indicating substantial spatial heterogeneity. The influence of women’s education is stronger in areas with more dynamic economic structures, while in less developed areas structural constraints moderate its impact. Stronger impacts are observed in areas with more dynamic labor markets, while weaker effects occur in regions with limited employment opportunities and higher reliance on informal sectors. These results underscore that gender-responsive development policies should not adopt a uniform provincial approach. Instead, spatially differentiated strategies are required. In lower-performing sub-districts, policy interventions should prioritize expanding access to women’s education alongside complementary economic support programs.